WACANA MERSUN, MAJUUG, DAN MATELISI DALAM GANCARAN MERSUN - Ririn Nurhayati, Ni Putu (Humanis, 2015)
Research "Discourse Mersun, Majuug, and Matelisi in prose Mersun" aims to identify and understand the social aspects contained in the Short Story Mersun, Majuug, and Matelisi. Theoretical basis used is sociological theory based on the opinion of literary Wellek and Warren. Methods and techniques used in this study consists of three phases namely, (1) Stage provision of data using methods refer to the techniques and methods capable of translation and recording. (2) Phase analysis of the data using qualitative methods and descriptive analytic techniques. (3) Stage presentation of the results of data analysis using informal methods and inductive deductive techniques. The results achieved in this study reveal the social aspects of the Short Story Mersun, Majuug, and Matelisi which include: ethical aspects, educational aspects, economic aspects, aspects of loyalty, and aspects of mutual cooperation.
Keywords: short story, structure, social aspects